Presidential Threshold Constitutionality Dilemma in Indonesia: A Comparative Study with Brazil - Anggreani, Shifa (Unisia, 2024)
This study examines the problematic constitutionality of the presidential threshold in Indonesia, which continues to be polemic in various circles. The presidential threshold, which regulates the threshold for presidential and vice-presidential nominations, has caused various controversies. Supporters argue that this threshold is important for creating a strong presidential system, whereas opponents argue that it limits the rights of political parties and the public to elect the leaders they want. This debate reflects dissatisfaction with regulations that are considered contrary to the principles of social justice and the Indonesian constitution. In the context of international comparison, Brazil, as one of the largest democracies, does not apply a presidential threshold that allows for wider political pluralism. This study aims to discuss the problematic constitutionality of the presidential threshold in Indonesia and explore alternative policies that support the presidential system without sacrificing political participation. The results of this comparative study show that a thresholdless system such as Brazil can increase political participation and pluralism, although it also has challenges such as political fragmentation. These findings provide an important perspective for Indonesia to evaluate and adapt its electoral system to strengthen its democracy.